Pengaruh Umur Bibit 25 Hari Terhadap Pertumbuhan dan Kandungan Karaginan - Maria Moi Daa; Marcelien Dj Ratoe Oedjoe; Felix Rebhung (Jurnal Akuatik, 2020)
This research has been carried out in Batobao Waters, Tesabela District, West Kupang District, Kupang Regency and the Laboratory of the Faculty of Marine Affairs and Fisheries as well as the Laboratory of the Faculty of Animal Husbandry, University of Nusa Cendana, Kupang from November 2019 to January 2020. The purpose of this study is to determine the effect of 25 days of seedlings on the growth and content of Khappapycus alvarezii carrageenan. Research on Khappapycus alvarezii seaweed cultivated using the long line method, namely with two treatments: A seed from Nature, treatment B 25 days old seedlings. Growth data obtained from the research were analyzed using paired samples t-test analysis. The results of this study indicated the effect of 25 days seed treatment on the growth and content of Khappapycus alvarezii carrageenan. The highest absolute growth was found in treatment B (25 days) which was 251 grams, and the lowest was in treatment A (natural) at 221.4 grams. While the carrageenan content showed a significant effect, namely the highest in treatment B (45%) followed by treatment A (20.6%). Based on these results it can be concluded that there is an effect of the age of the nursery on the growth and content of Khappapycus alvarezii carrageenan. Key words: Khappapycus alvarezii seaweed, growth, carrageenan content.